Systematic Literature Review: Green Marketing - Berlian, Umayya Hanif; Nurpratiwi, Embun Rahmah; Mu’ammar, Naufal; Dirgantara, I Made Bayu; Soesanto, Harry (Research Horizon, 2024)
This journal conducts a Systematic Literature Review on green marketing or what is often referred to as green marketing and its influence on business aspects and environmental aspects that focus on environmentally friendly products (green products) and the environment (environmental). Green marketing is the activity of producing and marketing products that are reusable and environmentally friendly. Recently, public awareness about environmental sustainability has increased, encouraging companies to use green marketing and green product practices. This journal systematically reviews the literature that reviews green marketing in business aspects, namely environmentally friendly products and environmental aspects. This journal is a literature review using the Watase Uake website. Initial data amounted to 173 articles published from 2014-2024 according to the Scopus database, then in this article, there were 55 journals analyzed using several criteria. This journal is an input for the development of further research, especially in the realm of green marketing in business and environmental aspects.